Impact of the Covid-19 Pandemic on the Mental Health and Lifestyle of Health Care Workers in Southern India - Mehak Agarwal; Prithvi Ravi; Chitra Ramesh; Judson Neslin (Medsci Publications, 2021)
Introduction: The Covid-19, just like any other Pandemic has been an extremely difficult time for people all over the world; however it has been the most challenging time for the frontline staff such as health care workers. It has not just led to changes in their work environment, but has also affected their lifestyle and mental health. Objective: We conducted this survey to analyse the impact of the covid-19 pandemic on the lifestyle and mental health of health care workers. Methodology: A cross-sectional study was conducted with the help of a questionnaire. A questionnaire was created and circulated via social media to various health care professionals. Response from participants was analysed using SPSS 16 version software and MS excel sheet. Result: The survey reported the impact on physical and mental health. It was studied that most health care Professionals, especially the ones working in a covid environment, experienced sleep disturbances, diet and weight change, change in the level of physical activity, bowel disturbances, smoking and alcohol habit changes, mood swings, anxiety, fear, inability to concentrate, fatigue/burnout from work. Conclusion: These changes affecting the lives of health care workers should be addressed as they can have permanent effects. Mental and physical health of medical professionals is essential, and attention should be extended to help them cope with their difficulties.